Chronic Thromboembolic Pulmonary Hypertension Perioperative Monitoring Using Phase‐Resolved Functional Lung (PREFUL)‐MRI. Issue 2 (24th February 2020) - Pöhler, Gesa H.; Klimes, Filip; Voskrebenzev, Andreas; Behrendt, Lea; Czerner, Christoph; Gutberlet, Marcel; Cebotari, Serghei; Ius, Fabio; Fegbeutel, Christine; Schoenfeld, Christian; Kaireit, Till F.; Hauck, Erik F.; et al.
Abstract : Background: The translation of phase‐resolved functional lung (PREFUL)‐MRI to routine practice in monitoring chronic thromboembolic pulmonary hypertension (CTEPH) still requires clinical corresponding imaging biomarkers of pulmonary vascular disease. Purpose: To evaluate successful pulmonary endarterectomy (PEA) via PREFUL‐MRI with pulmonary pulse wave transit time (pPTT). Study Type: Retrospective. Population: Thirty CTEPH patients and 12 healthy controls were included. Field Strength/Sequence: For PREFUL‐MRI a 2D spoiled gradient echo sequence and for DCE‐MRI a 3D time‐resolved angiography with stochastic trajectories (TWIST) sequence were performed on 1.5T. Assessment: Eight coronal slices of PREFUL‐MRI were obtained on consecutive 13 days before and 14 days after PEA. PREFUL quantitative lung perfusion (PREFULQ ) phases over the whole cardiac cycle were calculated to quantify pPTT, the time the pulmonary pulse wave travels from the central pulmonary arteries to the pulmonary capillaries. Also, perfusion defect percentage based on pPTT (QDPpPTT ), PREFULQ (QDPPREFUL ), and V/Q match were calculated. For DCE‐MRI, pulmonary blood flow (PBF) and QDPPBF were computed as reference. For clinical correlation, mean pulmonary arterial pressure (mPAP) and 6‐minute walking distance were evaluated preoperatively and after PEA. Statistical Tests: The Shapiro–Wilk test, paired two‐sided Wilcoxon rank sum test, Dice coefficient, and Spearman's correlation coefficient (ρ) were applied. Results: Median pPTT was significantly lower post PEA (139 msec) compared to pre PEA (193 msec), P = 0.0002. Median pPTT correlated significantly with the mPAP post PEA (r = 0.52, P < 0.008). Median pPTT was distributed more homogeneously after PEA: IQR pPTT decreased from 336 to 281 msec ( P < 0.004). Median PREFULQ ( P < 0.0002), QDPpPTT ( P < 0.0478), QDPPREFUL ( P < 0.0001) and V/Q match ( P < 0.0001) improved significantly after PEA. Percentage change of PREFULQ correlated significantly with percentage change of 6‐minute walking distance (ρ = 0.61; P = 0.0031) 5 months post PEA. Data Conclusion: Perioperative perfusion changes in CTEPH can be detected and quantified by PREFUL‐MRI. Normalization of pPTT reflects surgical success and improvement of PREFULQ predicts 6‐minute walking distance changes. Level of Evidence: 3 Technical Efficacy Stage: 2 J. Magn. Reson. Imaging 2020;52:610–619.